Some empirical notes on the Epo epidemic in professional cycling - Lodewijkx, H. F. M.; Brouwer, B. (Research Quarterly for Exercise and Sport, 2011)
The 1990-2010 period in professional cycling is labeled by some as the epo epidemic. Surprisingly, performance enhancement by epo and blood doping is not that clear-cut for endurance athletes, leading to the question whether doping indeed strongly influenced cyclists' performances from the 1990s onwards. We examined the records (1947-2008) of the Tour de France, Giro d'Italia, and Vuelta a España (N = 181) and assessed the time it took riders to win the race. The findings revealed normally distributed performances and linear and quartic relationships in victors' performances over time that correspond with Brewer's (2002) sociohistorical analysis of professional cycling, suggesting that effects of the epo epidemic on professional cyclists' achievements may be overestimated.